Women’s representation in The Pursuit of Happyness (2006) (Passage: Journal of English Language and Literature, 2025)
This article examines the representation of women in the film The Pursuit of Happyness (2006) through a narratology and feminism perspective. The primary objective of this study is to identify and analyse how a female character is constructed in terms of Linda’s presentation, characterization, and the power relations between male and female figures. Employing both visual and narrative discourse alongside a feminist perspective, this research seeks to reveal whether women are presented in equitable manner or instead reproduce patriarchal gender stereotypes. The results of the study show that since the film narratively focuses on the struggle of a single father, women are represented as supporting characters and do not have narrative space that can voice women’s struggle. Moreover, the elimination of women’s voice in the film emphasizes the construction of women’s monstrosity as defying the myth of good mother and wife in subordinate positions as supporting characters or are represented stereotypically.